Reduction in tissue plasmin: a new mechanism of action of narrowband ultraviolet B in psoriasis. (1st June 2015) - Metwally, D.; Sayed, K.; Abdel Hay, R.; Rashed, L.
Summary: Background: Plasmin (PL) is a potent inflammatory cell activator, and ultraviolet (UV)B has immunomodulatory effects on cutaneous inflammatory responses. There are no previous studies comparing the effect of narrowband (NB)‐UVB on tissue PL levels in psoriasis. Aim: To estimate the possible role of PL in the pathogenesis of psoriasis, and to evaluate the effect of NB‐UVB on tissue PL in psoriasis. Methods: This case–control study enrolled 21 patients with psoriasis and 20 clinically healthy volunteers matched for age and sex. Patients underwent 24 sessions of NB‐UVB radiation. Biopsy samples using a 4 mm punch were taken from all patients before and after treatment and from the controls for estimation of tissue PL level by ELISA. Results: Tissue PL was significantly upregulated in psoriasis before treatment (mean ± SD 1.73 ± 1.23 ng/mg protein) compared with controls (0.21 ± 0.15 ng/mg protein) ( P < 0.001). A statistically significant positive correlation ( P = 0.02) was found between the tissue PL before treatment and the Psoriasis Area and Severity Index. Patients received 24 sessions of NB‐UVB, with a mean cumulative dose of 23.25 ± 8.14 mJ/cm 2 . Tissue PL levels were reduced by a mean of 30.3% post‐treatment compared with baseline ( P < 0.001). The reduction in Pl levels was significantly correlated with the cumulative dose of NB‐UVB, and with the percentage reduction in PASI ( P < 0.001). Conclusions: Our study highlights the possible role played by tissue PL level in the pathogenesis of psoriasis. PL level appears to reflect disease severity, and is a possible marker of therapeutic efficacy of NB‐UVB on psoriatic skin.